2021
DOI: 10.3390/pharmaceutics13070966
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship and Molecular Docking of a Kunitz-Like Trypsin Inhibitor, Kunitzin-AH, from the Skin Secretion of Amolops hainanensis

Abstract: Kunitz-like trypsin inhibitors are one of the most noteworthy research objects owing to their significance in pharmacological studies, including anticarcinogenic activity, obesity regulation and anticoagulation. In the current study, a novel Kunitz-like trypsin inhibitor, Kunitzin-AH, was isolated from the skin secretion of Amolops hainanensis. The novel peptide displayed a modest trypsin inhibitory activity with the inhibitor constant (Ki) value of 1.18 ± 0.08 µM without inducing damage to healthy horse eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(78 reference statements)
2
6
0
Order By: Relevance
“…AH-884 is a variant of kunitz-like trypsin inhibitor peptide from the skin secretion of Amolops hainanensis, named Kunitzin-AH presenting trypsin inhibitory activity. The docking simulation of Trypsin with AH-884 has demonstrated that four (4) amino acid residues Ser789, Asp792, Lys702, and Tyr 681 trypsin bond to Arg1, Asn5 and Cys7 residues of the AH-884 [53]. These reported results matched up with the docking data of the current study that illustrated the involvement of Cerastokunin Cys16 and Asn17 in the interaction with trypsin.…”
Section: Discussionsupporting
confidence: 86%
“…AH-884 is a variant of kunitz-like trypsin inhibitor peptide from the skin secretion of Amolops hainanensis, named Kunitzin-AH presenting trypsin inhibitory activity. The docking simulation of Trypsin with AH-884 has demonstrated that four (4) amino acid residues Ser789, Asp792, Lys702, and Tyr 681 trypsin bond to Arg1, Asn5 and Cys7 residues of the AH-884 [53]. These reported results matched up with the docking data of the current study that illustrated the involvement of Cerastokunin Cys16 and Asn17 in the interaction with trypsin.…”
Section: Discussionsupporting
confidence: 86%
“…The total protein concentration was quantified using a BCA assay, and the yield of rFMB-BBTI was approximately 11.30 mg/L. The biological function of a protein is closely related to its conformation, and CD is often used to evaluate the structure and stability of designed proteins. , To evaluate the effect of recombinant expression on the structure of FMB-BBTI protein, the secondary structure of FMB-BBTI was predicted by PSIPRED platform (Figure E). Further, the secondary structures of FMB-BBTI and rFMB-BBTI were analyzed by CD (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…The shot-gun cloning was performed to isolate the prepropeptide encoding RNA, as described before [ 21 ]. In the 3′-RACE reaction, a nested universal primer (NUP) and a degenerate primer specially designed according to the highly conserved 5′-untranslated region of previously characterised peptide precursor cDNAs from closely-related Rana species (5′-ACTTTCYGAWTTRYAAGMCCAAABATG-3′, Y = C + T, W = A + T, R = A + G, M = A + C, B = T + C + G) were used in a segment of the 5′-untranslated region.…”
Section: Methodsmentioning
confidence: 99%